2016
DOI: 10.1038/srep27462
|View full text |Cite
|
Sign up to set email alerts
|

Stromal fibroblasts derived from mammary gland of bovine with mastitis display inflammation-specific changes

Abstract: Fibroblasts are predominant components of mammary stromal cells and play crucial roles in the development and involution of bovine mammary gland; however, whether these cells contribute to mastitis has not been demonstrated. Thus, we have undertaken biological and molecular characterization of inflammation-associated fibroblasts (INFs) extracted from bovine mammary glands with clinical mastitis and normal fibroblasts (NFs) from slaughtered dairy cows because of fractured legs during lactation. The functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…Extending our previous finding that stromal fibroblasts derived from mammary gland of bovine with mastitis display inflammation-specific changes 15, we here initially showed that INFs extracted from bovine mammary glands with clinical mastitis had different expression pattern regarding to several ECM proteins, chemokines and cytokines compared to NFs from dairy cows during lactation. Organ fibrosis is usually characterized by exaggerated production of ECM 2, and an abnormal inflammatory response can lead to over-production and deposition of ECM components, leading to fibrosis.…”
Section: Discussionsupporting
confidence: 61%
“…Extending our previous finding that stromal fibroblasts derived from mammary gland of bovine with mastitis display inflammation-specific changes 15, we here initially showed that INFs extracted from bovine mammary glands with clinical mastitis had different expression pattern regarding to several ECM proteins, chemokines and cytokines compared to NFs from dairy cows during lactation. Organ fibrosis is usually characterized by exaggerated production of ECM 2, and an abnormal inflammatory response can lead to over-production and deposition of ECM components, leading to fibrosis.…”
Section: Discussionsupporting
confidence: 61%
“…Primary BMECs were derived from healthy lactating bovine by our research group during previous research [17]. BMECs were recovered and cultured in DMEM/F12 with 10 % fetal bovine serum, 100 IU/mL of penicillin, and 100 µg/mL streptomycin (GibcoBRL, Grand Island, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Mammary tissue was obtained from dairy cows, with or without mastitis, and confirmed by macroscopic dissection, followed by microscopic examination, in our previous work [17]. The tissues were ground into powder in liquid nitrogen, and cells or tissue powders were lysed in PRO-PREP Protein Extraction Solution (iNtRON Biotechnology Inc., Gyeonggi-do, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Immortalized bovine mammary epithelial cells (MAC-T) [22] and primary bovine mammary epithelial cells (BMECs) isolated in our previous research [23] were cultured in complete DMEM/F12 medium (Gibco BRL, Grand Island, NY, USA) mixed with 10% fetal bovine serum, 100 IU/ml penicillin, and 100 µg/ml streptomycin (Gibco BRL) at 37°C in a humid incubator with 5% CO2. Inflammatory responses of MAC-T were induced by lipopolysaccharide (LPS) (Sigma-Aldrich, St Louis, MO, USA) at a final concentration of 10 ng/μl for 3 h or heatinactivated E. coli at a ratio of 1:1000 according to our previous publications [24,25].…”
Section: Cell Culture Treatment and Tissue Collectionmentioning
confidence: 99%
“…Inflammatory responses of MAC-T were induced by lipopolysaccharide (LPS) (Sigma-Aldrich, St Louis, MO, USA) at a final concentration of 10 ng/μl for 3 h or heatinactivated E. coli at a ratio of 1:1000 according to our previous publications [24,25]. Tissues from Holstein dairy cows were extracted in our recent research [23].…”
Section: Cell Culture Treatment and Tissue Collectionmentioning
confidence: 99%